2017
DOI: 10.1038/s41598-017-13674-9
|View full text |Cite
|
Sign up to set email alerts
|

Affecting long-term fear memory formation through optical control of Rac1 GTPase and PAK activity in lateral amygdala

Abstract: Fear conditioning, a behavioral model for studying fear-related disorders, is believed to be formed by alterations of synaptic efficacy mediated by changes in synaptic transmission and neuronal morphology in lateral amygdala (LA). Rac GTPase and its downstream effector p21-activated kinase (PAK) are involved in such key neuronal functions. Here we show that optical activation of Rac1 GTPase using photoactivatable form of Rac1 (PA-Rac1) in amygdala led to phosphorylation of PAK and inhibition of long-term but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…We also showed that Rac1 inhibition, similar to inhibition of TrkB, rescued anxiety-related velocity of tsc2 vu242/vu242 . In line with our results, Rac1 overactivation was previously shown to inhibit the formation of long-term fear conditioning memory (42). Rac1 is required for commissural axon development specifically in the cortex and controls axon crossing through the AC and corpus callosum in mice (43,44).…”
Section: Discussionsupporting
confidence: 92%
“…We also showed that Rac1 inhibition, similar to inhibition of TrkB, rescued anxiety-related velocity of tsc2 vu242/vu242 . In line with our results, Rac1 overactivation was previously shown to inhibit the formation of long-term fear conditioning memory (42). Rac1 is required for commissural axon development specifically in the cortex and controls axon crossing through the AC and corpus callosum in mice (43,44).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated a role for Rac1 GTPase in learning and memory formation in the amygdala. Light stimulation of photoactivatable Rac1 (PA-Rac1) during auditory fear conditioning in the LA led to an increase in PAK phosphorylation and to an impairment in long-but not in short-term auditory fear conditioning memory (Das et al, 2017). Inhibiting the downstream effector PAK in LA enhanced longbut not short-term fear conditioning memory.…”
Section: Rac1 Gtpase In Learning and Memory Formationmentioning
confidence: 99%
“…Rac1 activation on the other hand accelerated memory decay within 24 h. Moreover, expression of active Rac1 produced more lamellipodia-like synapses with a large spine head and overexpression of Rac1-DN led to a reduced spine density, with more long and thin filopodia-like spines. Activation of Rac1 in LA impaired long- but not short-term memory formation (Das et al, 2017 ). In Drosophila, Rac1 also mediates forgetting (Shuai et al, 2010 ; Dong et al, 2016 ).…”
Section: Evidence For a Role For Actin Cytoskeleton And Its Regulatormentioning
confidence: 99%